2021
DOI: 10.1038/s41467-021-25991-9
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the functional role of DNA demethylation at specific promoters by targeted steric blockage of DNA methyltransferase with CRISPR/dCas9

Abstract: Despite four decades of research to support the association between DNA methylation and gene expression, the causality of this relationship remains unresolved. Here, we reaffirm that experimental confounds preclude resolution of this question with existing strategies, including recently developed CRISPR/dCas9 and TET-based epigenetic editors. Instead, we demonstrate a highly effective method using only nuclease-dead Cas9 and guide RNA to physically block DNA methylation at specific targets in the absence of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 133 publications
4
35
0
Order By: Relevance
“…AFF3 and ZFP281) that are necessary to activate the enhancer function for Meg3 , and the repressed Meg3 expression led to hypermethylation at maternal Meg3 -DMR ( 20 , 21 ). It is also suggested that steric hindrance caused by stable expression of Cas9-related artificial proteins triggers epigenetic alterations by interfering with the binding of endogenous proteins at target sites, which could be the cause of the spread of DNA methylation into IG CGI in their experiment ( 53 ). Further studies with stable expression of catalytically inactive dCas9-TET1CD or dCas9-DNMT3A with gRNAs targeting IG TRE are required to resolve this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…AFF3 and ZFP281) that are necessary to activate the enhancer function for Meg3 , and the repressed Meg3 expression led to hypermethylation at maternal Meg3 -DMR ( 20 , 21 ). It is also suggested that steric hindrance caused by stable expression of Cas9-related artificial proteins triggers epigenetic alterations by interfering with the binding of endogenous proteins at target sites, which could be the cause of the spread of DNA methylation into IG CGI in their experiment ( 53 ). Further studies with stable expression of catalytically inactive dCas9-TET1CD or dCas9-DNMT3A with gRNAs targeting IG TRE are required to resolve this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher’s test for enrichment revealed that a greater number of significant FAP related CpG sites were identified than expected by chance in our individual analyses of TCGA-COAD ( P = 1.19E −20 ), GSE193535 ( P = 1.22E −16 ) and ColoCare ( P = 7.64E −21 ). While most of the DMRs were concordant, 10.36% [ 37 ] of the 358 DMRs displayed discordance for direction of effect in at least two cancer cohorts and FAP patients. This included DLEU1 , which was hypomethylated in FAP versus normal colon organoids, but significantly hypermethylated in all three tumor vs NAT analyses (Additional file 4 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, analysis of important driver mutations for CRC development in this epithelial cell compartment has the potential to better identify DMRs relevant to early CRC biology. Thus, the identification of downstream molecular events related to APC has the potential to lead to the identification of genes critical to tumor development [ 35 ], some of which may be modifiable through drug targeting [ 36 ] or gene editing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of promoter CpG islands is a hallmark of cancer progression and typically correlates with transcriptional repression of the associated gene, as illustrated in Figure 2A ( 25 ). However, it is important to note that the exact role and relationship between methylation and gene expression remains unresolved, and seems to depend highly on the specific context ( 26 ). Promoter hypermethylation is commonly associated with a decrease in transcriptional activity and thought to alter the recruitment of regulatory proteins to the underlying DNA sequence, subsequently blocking transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%